2017
DOI: 10.1002/fes3.110
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and elemental concentrations of 22 rice cultivars grown under alternate wetting and drying conditions at three field sites in Bangladesh

Abstract: As the global population grows, demand on food production will also rise. For rice, one limiting factor effecting production could be availability of fresh water, hence adoption of techniques that decrease water usage while maintaining or increasing crop yield are needed. Alternative wetting and drying (AWD) is one of these techniques. AWD is a method by which the level of water within a rice field cycles between being flooded and nonflooded during the growth period of the rice crop. The degree to which AWD af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 38 publications
4
43
2
Order By: Relevance
“…Importantly, both authors agree that AWD increases the harvest index; an observation was also made by Norton, Travis, et al. ().…”
Section: Alternate Wetting and Dryingsupporting
confidence: 74%
See 2 more Smart Citations
“…Importantly, both authors agree that AWD increases the harvest index; an observation was also made by Norton, Travis, et al. ().…”
Section: Alternate Wetting and Dryingsupporting
confidence: 74%
“…() reported AWD caused a significant average grain mass increase of 9.8% and 9% compared to continually flooded over their two‐study years. Another study by the same authors (Norton et al., ) testing AWD on 22 cultivars in three sites in 2014 found AWD increased yield overall by 6.5% with individual site increases of 18.4% in Mymensingh, 8.7% in Madhupur, and no difference in Rajshahi. Oliver et al.…”
Section: Alternate Wetting and Dryingmentioning
confidence: 95%
See 1 more Smart Citation
“…Yang et al (2009Yang et al ( , 2017 reported that WMD could cause reduction in grain As level and Cd content. Norton et al (2017) found that safe AWD decreased grain As concentration by 14 to 26% while increasing grain Cd concentration by 28 to 67%. We observed that the WMD regime significantly reduced As content in grains (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…4). It was observed that there were significant two-way interactions about the influence of a safe AWD on grain Cd concentration among experimental site, treatment, and rice genotype (Norton et al, 2017). Yang et al (2009) reported that WMD (rewatered when soil water potential decreased to −20 kPa) irrigation, in contrast with WW, reduced Cd content in the grain and in milled rice by 19 to 21% and 40%, respectively, and increased Cd accumulation in the roots.…”
Section: Discussionmentioning
confidence: 99%